The Three Sisters: the first three Beatitudes as guiding an embodied response to the discovery of the unmarked graves at residential schools across Canada in 2021 - Millar, Elizabeth (Practical theology, 2023)
Using the Indigenous Three Sisters gardening technique as a guiding metaphor, this paper will explore a wholly embodied response to the disturbing headlines of the discovery of hundreds of unmarked graves at residential schools across Canada in 2021. Just as the Indigenous Three Sisters cooperate together for mutual flourishing, the Beatitudinal trio of humility, grief, and meekness will be promoted as characteristics of a wholly embodied response to this specific issue and the large issue it represents, which is an oppressive and troubled historic relationship between Indigenous and white settlers. This paper will use Terry A. Veiling’s double exegetical approach of ‘on earth as it is in heaven’ as the underlying practical theology framework. Perspectives of various Indigenous Canadian theologians along with hopeful stories of white settler Canadian church leaders whose performative and incarnational responses resemble the three sisterly Beatitudes will be included throughout. I see the flourishing of the Three Sisters together as a helpful and practical metaphor for the Canadian church as we consider how humility, grief, and meekness can help us neighbour well with Indigenous people.